Evaluasi dan Rekomendasi Perbaikan Desain Antarmuka Pengguna Aplikasi Lumajang Bersahabat menggunakan Metode Usability Testing dan Pendekatan Human Centered Design (HCD) - Muhammad Irfan Nugraha; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Lumajang Bersahabat is the official e-Government application for the Lumajang Regency Government based on a mobile application that can be widely used by the public to obtain information about Lumajang. The usability evaluation of the application that has been carried out so far is limited to involving the internal organization of the organization with a conventional approach. The developer requires usability evaluation from external parties, namely the community as users to get input and materials for developing the Lumajang Lumajang application in the future. This study aims to testing Lumajang Bersahabat that involves users with usability testing methods and the Human Centered Design (HCD) approach which produces recommendations for user interface improvements. Usability testing produces values from aspects of effectiveness, efficiency, and user Satisfaction and Human Centered Design (HCD) as an approach to product design that focuses on user testing. In the usability evaluation phase I resulted in an Effectiveness value is 71.2%, an efficiency value is 65.5%, and user Satisfaction with an SUS score 46.25. The Human Centered Design process produces an interface improvement design in the form of a prototype to solve 9 usability problems and add 7 new features according to user needs. Phase II usability testing on the interface improvement prototype resulted in an increase in the Effectiveness value to 98.4%, the efficiency value to 97.5%, and user Satisfaction with an SUS score of 84.58.